2006
DOI: 10.1080/15572536.2006.11832708
|View full text |Cite
|
Sign up to set email alerts
|

Fungal spore diversity of arbuscular mycorrhizal fungi associated with spring wheat: effects of tillage

Abstract: We investigated the influence of tilling, N fertilization and crop stage on arbuscular mycorrhizae (AM) fungal species diversity in a wheat monoculture in the Pampa region of Argentina. Glomalean spores were isolated by wet sieving and decanting from conventionally tilled and nontilled soils cropped with wheat with or without N fertilization, at three phenological stages of the crop (tilling, flowering and grain filling) and fallow. Morphological characterization yielded at least 24 AM fungi taxa in the field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…Hausmann and Hawkes (2010) manipulated the order of plant species establishment experimentally and demonstrated that the first-established plant species filtered the initial AM fungal pool, thereby determining the symbiotic AM fungal assemblages of later-established plant species. This temporal sorting process would be reinforced by the effects of plant phenology and growth on AM fungal colonization rate, spore diversity and relative abundance (Johnson-Green, Kenkel, & Booth, 1995;Schalamuk, Velazquez, Chidichimo, & Cabello, 2006). Since AM fungal propagules (hyphae and spores) can survive and colonize plant roots even after one year of residence in the soil (McGee, Pattinson, Heath, Newman, & Allen, 1997), we examined the hypothesis that the AM fungal community responds to past or present spatial patterns of the plant community.…”
mentioning
confidence: 99%
“…Hausmann and Hawkes (2010) manipulated the order of plant species establishment experimentally and demonstrated that the first-established plant species filtered the initial AM fungal pool, thereby determining the symbiotic AM fungal assemblages of later-established plant species. This temporal sorting process would be reinforced by the effects of plant phenology and growth on AM fungal colonization rate, spore diversity and relative abundance (Johnson-Green, Kenkel, & Booth, 1995;Schalamuk, Velazquez, Chidichimo, & Cabello, 2006). Since AM fungal propagules (hyphae and spores) can survive and colonize plant roots even after one year of residence in the soil (McGee, Pattinson, Heath, Newman, & Allen, 1997), we examined the hypothesis that the AM fungal community responds to past or present spatial patterns of the plant community.…”
mentioning
confidence: 99%
“…In Argentina, earlier studies have found less management of AMF to increase plant productivity (Covacevich and Echeverría 2009). It is known that soils of the Pampas region present high native AMF that colonize crop plants under different management systems (Covacevich et al 2006(Covacevich et al , 2007Schalamuk et al 2006;Covacevich and Echeverría 2008); however, they are not yet manipulated. To avoid decreases in the grassland productivity, which leads to decline livestock production, new studies including AMF ecology and on the impact of agricultural practices on AMF symbiosis pointed to a selective decrease of viable spore number with glyphosate applications in native grasslands (in the Flooding Pampa), resulting in altered AMF community structure.…”
Section: The Mycorrhizal Symbioses In Agro-ecosystemsmentioning
confidence: 99%
“…cag.wvu.edu). Frequency of occurrence for AM-fungal spore morphotypes was calculated according to Schalamuk et al (2006).…”
Section: Enumeration and Isolation Of Am-fungal Sporesmentioning
confidence: 99%